Montréal: Towards a post-industrial reinvention. (March 2019) - Moser, Sarah; Fauveaud, Gabriel; Cutts, Adam
Abstract: Following the decline of Montréal's manufacturing sector, shipping, and its status as Canada's banking center, a growing portion of the city's economy is tied to the knowledge economy, particularly education, arts, and R&D. With four major universities, comparatively low costs of living, lucrative creative industries, and a vibrant arts scene, in recent years the city government has devised strategies to more formally leverage Montréal's assets in order to expand the knowledge economy. This article first sketches out the urban impacts of some of Montréal's major economic and social transitions, then turns to examine how the city is attempting to build on its assets as part of the official pivot towards fostering a knowledge economy. We examine policies and organizations intended to expand the knowledge economy, how they are impacting the city, and some key tensions and challenges facing the city as it tries to reinvent itself. While the city is experiencing a boom in the knowledge and creative economies, the benefits of this boom are unevenly distributed and they may be undermined by several factors, including gentrification. Highlights: After decades of decline, Montréal is attempting to build on its assets to foster a knowledge economy. We outline key challenges facing Montréal, including neoliberalization, gentrification, condoization, and corruption. Our paper examines policies and organizations intended to expand the knowledge economy, how they are impacting the city. We examine how Québec's nationalist streak permeates politics, culture, and procurement.